Poor venous outflow profiles increase the risk of reperfusion hemorrhage after endovascular treatment. Issue 1 (January 2023) - Winkelmeier, Laurens; Heit, Jeremy J; Adusumilli, Gautam; Geest, Vincent; Guenego, Adrien; Broocks, Gabriel; Prüter, Julia; Gloyer, Nils-Ole; Meyer, Lukas; Kniep, Helge; Lansberg, Maarten G; Albers, Gregory W; et al.
To investigate whether unfavorable cerebral venous outflow (VO) predicts reperfusion hemorrhage after endovascular treatment (EVT), we conducted a retrospective multicenter cohort study of patients with acute ischemic stroke and large vessel occlusion (AIS-LVO). 629 AIS-LVO patients met inclusion criteria. VO profiles were assessed on admission CT angiography using the Cortical Vein Opacification Score (COVES). Unfavorable VO was defined as COVES ≤ 2. Reperfusion hemorrhages on follow-up imaging were subdivided into no hemorrhage (noRH), hemorrhagic infarction (HI) and parenchymal hematoma (PH). Patients with PH and HI less frequently achieved good clinical outcomes defined as 90-day modified Rankin Scale scores of ≤ 2 (PH: 13.6% vs. HI: 24.6% vs. noRH: 44.1%; p < 0.001). The occurrence of HI and PH on follow-up imaging was more likely in patients with unfavorable compared to patients with favorable VO (HI: 25.1% vs. 17.4%, p = 0.023; PH: 18.3% vs. 8.5%; p = <0.001). In multivariable regression analyses, unfavorable VO increased the likelihood of PH (aOR: 1.84; 95% CI: 1.03–3.37, p = 0.044) and HI (aOR: 2.05; 95% CI: 1.25–3.43, p = 0.005), independent of age, sex, admission National Institutes Health Stroke Scale scores and arterial collateral status. We conclude that unfavorable VO was associated with the occurrence of HI and PH, both related to worse clinical outcomes.